Fatores que influenciam o desempenho de exportações de carne bovina dos países com base em sua competitividade, recursos e capacidades - Biscola, Paulo Henrique Nogueira (2022)
Exports have an impact on improving the performance of companies and on the economic growth of countries. They grow as a result of global changes, which will impact the food market and, more specifically, beef, one of the most important products on the export agenda of several countries. Strategic decisions related to exports are mainly based on internal resources and external forces to the companies. To this end, the theories of resource-based view (RBV) and competitive advantage of nations (CAN) were studied. This thesis seeks to answer the question of which factors influence the beef exports performance of countries based on their competitiveness, resources and capabilities. The potential impacts of countries' competitiveness (CC) on export performance (EP) were studied, as well as the impacts of CC on the resources and capabilities of the production chain, which led to the proposal of a theoretical model and research hypotheses. Two samples of exporting countries were used, one for the period 2009 to 2014, with 30 countries, which are responsible for 97% of the total exported value of beef in the year, and another for the period 2014 to 2019, with 37 countries, responsible for 94.6% of the total exported value of beef in the year. Therefore, the study approached a time interval of 11 years, between the years 2009 and 2019. Variables and international databases were identified. Exploratory factorial analyzes and Partial Least Squares Structural Equation Modeling (PLS-SEM) were performed. As main results, the resources and capabilities of the productive chains that most interfere in the export performance are presented, which are associated with productivity, more specifically the average carcass weight, slaughter and beef production. The external aspects associated with the CC that most affect the beef exports performance were also defined, which are: institutions; financial market development; higher education and training; labor market efficiency; goods market efficiency; business sophistication and R&D innovation. At the end, it was presented theoretical and methodological contributions, managerial implications, limitations and suggestions for future studies.